Improving Access to Maternal Healthcare Among Female Employees: Quantitative Analysis of the impact of The National Health Insurance Scheme - Pius U. Angioha; Thomas A. Omang; Uduakobong P. Akpabio; James A. Ogar; Tersoo Asongo; Francis Ibioro (PT Mattawang Mediatama Solution, 2021)
This study examines the correlation between the national health insurance scheme and access to national health care among female employees in Federal Institutions in Calabar cross river state, Nigeria. The study specifically examines the extent to which the national health insurance scheme reduces the cost of health and Enrollment in the NHIS relates to access to maternal healthcare. Two hypotheses were raised for the study. The survey research design was adopted in collecting data from 400 samples from a population of 9201 female employees of the federal institutions in Calabar cross river state. The instrument of data collection was the questionnaire. Data collected was analyzed using descriptive and correlation analysis. Results revealed that the national health insurance scheme reduced health cost relates to access to maternal healthcare. Results also indicated that Enrollment in NHIS significantly relates to access to maternal health. Based on this result, the study recommends, amongst others, that there is a need for government to improve on health funding as this will help improve access to various provisions of the scheme as it relates to maternal health